Potential activity of aqueous extract of culinary-medicinal lion's mane mushroom, hericium erinaceus (Bull.: Fr.) Pers. (Aphyllophoromycetideae) in accelerating wound healing in rats - Abdullah, M.A.; Fard, A.A.; Sabaratnam, V.; Wong, K.H.; Kuppusamy, U.R.; Abdullah, N.; Ismail, S. (2011)
This study was conducted to evaluate the effects of topical application of aqueous extract of Hericium erinaceus fruiting bodies (HEFB) on the rate of wound healing enclosure and histology of the healed wound. Five groups of male Sprague-Dawley rats were experimentally wounded in the posterior neck area. A uniform wound area of 2.00 cm in diameter, using a circular stamp, was excised from the nape of the dorsal neck of all rats with the aid of a round seal. The animal groups were topically treated, respectively, with 0.2 mL each of sterilized distilled water (sdH(2)O); Intrasite gel; and 20, 30, and 40 mg/mL HEFB. Macroscopically, those rats whose wounds were dressed with HEFB and those in the Intrasite gel-treated group healed earlier than those treated with sdH(2)O. Histological analysis of healed wounds dressed with HEFB showed less scar width at wound enclosure and the healed wound contained fewer macrophages and more collagen with angiogenesis, compared to wounds dressed with sdH(2)O. In conclusion, wounds dressed with HEFB significantly enhanced the acceleration of wound healing enclosure in rats.